Ba2HgTe5: a Hg-based telluride with giant birefringence induced by linear [HgTe2] units. Issue 19 (18th August 2022) - Sun, Mengran; Yao, Jiyong
Abstract : Ba2 HgTe5, the first Hg-based telluride birefringent material, was successfully synthesized. The analysis of the response electron distribution anisotropy illustrates that the large birefringence of Ba2 HgTe5 originates from the linear [HgTe2 ] unit. Abstract : In this work, Ba2 HgTe5, as the first compound identified in the Ba/Hg/Te system, has been successfully synthesized via a solid-state reaction. It crystallizes in the orthorhombic space group pnma and exhibits a 0D structure composed of linear [HgTe2 ] units and V-shaped [Te3 ] units arranged in an alternating manner. The experimental and theoretical calculation results indicate that Ba2 HgTe5 is a potential IR birefringent material, possessing a moderate band gap (1.28 eV), giant optical anisotropy (Δ n cal = 0.643@2090 nm), a low melting point (576 °C), and congruent-melting behavior. The results of the structure–property relationship reveal that the band gap of Ba2 HgTe5 is primarily defined by the Te p orbitals in the [Te3 ] unit. Further, the analysis of the response electron distribution anisotropy (REDA) illustrates that the large birefringence of Ba2 HgTe5 is induced mainly from the linear [HgTe2 ] unit (about 90% contribution). This work demonstrates for the first time the rationality of the [HgTe2 ] group as the gene for designing IR birefringent materials.